2017
DOI: 10.1108/pr-05-2016-0105
|View full text |Cite
|
Sign up to set email alerts
|

HRM practices that support the employment and social inclusion of workers with an intellectual disability

Abstract: This study examines how HRM practices enhance and/or impede the employment, participation, and wellbeing of workers with intellectual disabilities in three hotels located in Australia. The research employs a case study methodology, including interviews with three HR managers, three department managers, 17 workers with intellectual disabilities, and focus groups of 16 supervisors and 24 work colleagues. We employ social exchange theory and theory on social climate to explore the social inclusion of workers with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 56 publications
(120 reference statements)
3
44
0
4
Order By: Relevance
“…Next, creating an environment that is both healthy and safe to applicants with a disability is essential (Bengisu & Balta, 2011). Research has shown emotional support from peers and supervisors play an integral role in the success of a proposed work task (Kulkarni and Lengnick-Hall, 2011; Hedley et al, 2017; Meacham, Cavanagh, Shaw, & Bartram, 2017), and can serve as an important role in reducing social isolation (Vornholt, Uitdewilligen, & Nijhuis, 2013) for individuals with a disability. As such, organizations and their staff need to facilitate an environment that is both open and supportive of diversity through social responsibility policies, practices, and initiatives (Meacham et al, 2017: 1477).…”
Section: Discussion Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, creating an environment that is both healthy and safe to applicants with a disability is essential (Bengisu & Balta, 2011). Research has shown emotional support from peers and supervisors play an integral role in the success of a proposed work task (Kulkarni and Lengnick-Hall, 2011; Hedley et al, 2017; Meacham, Cavanagh, Shaw, & Bartram, 2017), and can serve as an important role in reducing social isolation (Vornholt, Uitdewilligen, & Nijhuis, 2013) for individuals with a disability. As such, organizations and their staff need to facilitate an environment that is both open and supportive of diversity through social responsibility policies, practices, and initiatives (Meacham et al, 2017: 1477).…”
Section: Discussion Questionsmentioning
confidence: 99%
“…Research has shown emotional support from peers and supervisors play an integral role in the success of a proposed work task (Kulkarni and Lengnick-Hall, 2011; Hedley et al, 2017; Meacham, Cavanagh, Shaw, & Bartram, 2017), and can serve as an important role in reducing social isolation (Vornholt, Uitdewilligen, & Nijhuis, 2013) for individuals with a disability. As such, organizations and their staff need to facilitate an environment that is both open and supportive of diversity through social responsibility policies, practices, and initiatives (Meacham et al, 2017: 1477). As seen during the ice breaker, Julie used self-deprecating humour to generate social engagement along with the trainers interjecting with phrases of encouragement (e.g., ‘that's wonderful!’ or ‘that's really exciting!’).…”
Section: Discussion Questionsmentioning
confidence: 99%
“…Although there is some research on the inclusion of people with SND in the workplace (e.g. Dwertmann and Boehm, 2016;Meacham, Cavanagh, Shaw and Bartram, 2017), we still know little about the work engagement of employees with children with SND (Li, Shaffer, and Bagger, 2015;Stewart, 2013). Recent research studies have consistently shown that these parents experience heavier caregiving duties than parents of typically developing children and, as a result, they are more likely to experience mental health and emotional distress (Deater-Deckard, 2004;Morris, 2014;U.S.…”
Section: Introductionmentioning
confidence: 99%
“…This may be associated with scholarly attempts to analyse most helping behaviours as part of wider reciprocal interactions (Han et al, 2018). Indeed, majorly investigated through the lense of SET (Cropanzano et al, 2017), helping is mostly based on the principle that people "reap the seeds that they sow" (Meacham et al, 2017(Meacham et al, , p. 1479. In this article, the notion of SET is extended to emphasise its other-oriented dimensions where any benefits in the process of help are valued as symbols of concern for others as opposed to expectations of returns (see: Colbert et al, 2016).…”
mentioning
confidence: 99%